PENGARUH PUPUK KANDANG KAMBING DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MENTIMUN JEPANG (Cucumis sativus L. var japanese) - Zain, Agisniati; Nurrachman, Nurrachman; Isnaini, Mulat (AGROTEKSOS, 2023)
This study aims to determine the effect of goat manure and NPK fertilizer on the growth and yield of Japanese cucumber (Cucumis sativus L. var japonese). The experiment was designed using a factorial randomized block design (RBD) with two treatment factors. The first factor was goat manure (K) which consisted of 3 levels, namely K0 (without goat manure), K1 (240 g/plant), and K2 (480 g/plant). The second factor is NPK fertilizer (P) consisting of 3 levels, namely P0 (without NPK), P1 (4.8 g/plant), and P2 (7.2 g/plant). From the two factors above, 9 treatment combinations were obtained. Each treatment combination was repeated 3 times, resulting in 27 experimental plots. Data obtained from the experiment were analyzed using Analysis of Variant 5% (ANNOVA). There were significantly different treatments, so it was continued with the BNJ test at the 5% level. The results of the analysis of the diversity of treatments of goat manure and NPK fertilizer had a significant effect on the number of fruit, fruit weight per plot, and wet chestnut weight. The number of fruit shown in the K1P1 treatment combination was 9.66 fruit, the highest fruit weight per plot was in the K2P2 treatment combination, namely 15.86 kg, the best wet chestnut weight in the treatment combination was 706.06 g. The NPK fertilizer treatment had a significant effect on the rate of increase in the number of leaves and the highest dry matter weight was shown by the P1 treatment. The goat manure treatment had a significant effect on the highest number of fruit in the K1 treatment, namely 9.24 fruit.   Keywords: Japanese cucumber, goat manure, NPK fertilizer